Adaptive kernel methods to simulate quantum phase space flow - Lopez, H.; Donoso, A. (Condensed Matter Physics, 2006)
A technique for simulating quantum dynamics in phase space is discussed. It makes use of ensembles of
classical trajectories to approximate the distribution functions and their derivatives by implementing Adaptive
Kernel Density Estimation. It is found to improve the accuracy and stability of the simulations compared to
more conventional particle methods. Formulation of the method in higher dimensions is straightforward.